2003
DOI: 10.1001/jama.290.7.912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High-Fat Ketogenic Diet on Plasma Levels of Lipids, Lipoproteins, and Apolipoproteins in Children

Abstract: HE KETOGENIC DIET IS A HIGHfat low-carbohydrate adequate protein diet first developed 8 decades ago for the management of difficult-to-control seizures in children. 1 Recent studies have documented the short-term and longterm benefits of this diet in improving seizure control. 2-4 An evaluation by the Blue Cross/Blue Shield Technology Center reported 5 ". .. the diet's effectiveness in providing seizure control for children with difficult-to-control seizures has remained as good, or better than any of the newe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
155
9
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(188 citation statements)
references
References 35 publications
14
155
9
10
Order By: Relevance
“…In previous short-term studies, increased plasma cholesterol levels were observed after 9 wk of diet (2), whereas at that time point plasma triglyceride levels were lower. Also, in both adults and children with refractory epilepsy, KD was associated with increased plasma cholesterol and triglyceride levels (24,38). Furthermore, the increased plasma cytokine concentrations in our study suggest a systemic proinflammatory state in longterm KD-fed mice.…”
Section: Discussionsupporting
confidence: 51%
“…In previous short-term studies, increased plasma cholesterol levels were observed after 9 wk of diet (2), whereas at that time point plasma triglyceride levels were lower. Also, in both adults and children with refractory epilepsy, KD was associated with increased plasma cholesterol and triglyceride levels (24,38). Furthermore, the increased plasma cytokine concentrations in our study suggest a systemic proinflammatory state in longterm KD-fed mice.…”
Section: Discussionsupporting
confidence: 51%
“…KD may cause hypercholesterolemia, hypertriglyceridemia, and elevation of apolipoprotein B-containing lipoprotein. 27 The long-term effect of KD-induced dyslipidemia on vascular structure and atheroma formation remains unclear. Although it appears to have no effect on the carotid intima-media thickness and elastic properties after 12 months of KD treatment, 28 Doppler studies and echocardiogram may be necessary in the presence of chronic dyslipidemia and to screen for cardiomyopathy.…”
Section: Dyslipidemia and Cardiovascular Complicationsmentioning
confidence: 99%
“…The longterm effects of a high-fat diet in mice have not been thoroughly investigated. In humans, the KD has been associated with increased risk of coronary heart disease (Best et al, 2000;Bergqvist et al, 2003;Dashti et al, 2003;Kwiterovich et al, 2003) among other adverse effects. It is unclear whether such adverse events played a role in the eventual death of KD fed Aldh5a1 −/− mice.…”
Section: Lifespanmentioning
confidence: 99%